THE THEATRE OF DECEPTION: NABOKOV’S EXPLORATION OF HUMAN NATURE IN HIS SECOND NOVEL “KING, QUEEN, KNAVE” (British Journal of Global Ecology and Sustainable Development, 2025)
Vladimir Nabokov’s “King, Queen, Knave” (1928) marks a key stage in his literary evolution, blending innovative narrative techniques with a deep exploration of human nature and bourgeois society. This study examines the novel’s reinterpretation of the adultery motif, its complex characters—Dreyer, Martha, and Franz—and its interplay of reality and illusion. Using semiotic, psychological, and structural analysis, the article highlights Nabokov’s mastery of literary craftsmanship and his use of intertextuality, theatricality, and duality. The novel’s playful style and unexpected resolution challenge readers to reflect on identity, morality, and existence. “King, Queen, Knave” not only influenced Nabokov’s later works but also solidified his unique artistic vision, making it a cornerstone of modern literature.